2005
DOI: 10.1029/157gm13
|View full text |Cite
|
Sign up to set email alerts
|

The spectral-element method in seismology

Abstract: We present the main properties of the spectral-element method, which is well suited for numerical calculations of synthetic seismograms for three-dimensional Earth models. The technique is based upon a weak formulation of the equations of motion and combines the flexibility of a finite-element method with the accuracy of a pseudospectral method. The mesh is composed of hexahedral elements and honors the main discontinuities in the Earth model. The displacement vector is expressed in each element in terms of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
120
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 69 publications
0
120
0
Order By: Relevance
“…The SEM is based on a weak formulation of the seismic-wave equation that guarantees very accurate modeling of surface waves (e.g., Komatitsch et al, 2005). Moreover, the method uses high-order Lagrange polynomials to interpolate the wavefield, together with Gauss-Lobatto-Legendre (GLL) quadrature, both defined on the same GLL points, thus leading to a perfectly diagonal mass matrix.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SEM is based on a weak formulation of the seismic-wave equation that guarantees very accurate modeling of surface waves (e.g., Komatitsch et al, 2005). Moreover, the method uses high-order Lagrange polynomials to interpolate the wavefield, together with Gauss-Lobatto-Legendre (GLL) quadrature, both defined on the same GLL points, thus leading to a perfectly diagonal mass matrix.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the highdegree Lagrange polynomials assure exponential spatial accuracy. Thorough reviews of the SEM in seismology can be found, e.g., in Komatitsch et al (2005), Chaljub et al (2007), Tromp et al (2008), andFichtner (2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has been subsequently applied in many areas of seismology (e.g., Komatitsch et al, 2002;Chaljub et al, 2003;Komatitsch et al, 2004). A critical issue for the successful application of SEM lies in the design of a good mesh (e.g., Komatitsch et al, 2005). Lee et al (2008) introduced a new mesh implementation using so-called control layers to improve mesh quality and the related numerical stability of the explicit time integration scheme.…”
Section: Realistic Topography and Basin Structurementioning
confidence: 99%
“…The method has been subsequently applied in many areas of seismology (see, e.g., Komatitsch et al [2002], [2004] and Chaljub et al [2003]). The biggest challenge for the successful application of the SEM in the case of complex geological structures lies in the design of the mesh (Komatitsch et al, 2005). Lee, Chen, Liu, et al (2008) presented a new mesh implementation to improve mesh quality and related numerical stability.…”
Section: Introductionmentioning
confidence: 99%